Factors associated with biomedical research participation within community‐based samples across 3 National Cancer Institute–designated cancer centers. Issue 5 (7th January 2020) - Barrett, Nadine J.; Rodriguez, Elisa M.; Iachan, Ronaldo; Hyslop, Terry; Ingraham, Kearston L.; Le, Gem M.; Martin, Kelly; Haring, Rodney C.; Rivadeneira, Natalie A.; Erwin, Deborah O.; Fish, Laura J.; Middleton, Deirdre; et al.
Abstract : Background: Engaging diverse populations in biomedical research, including biospecimen donation, remains a national challenge. This study examined factors associated with an invitation to participate in biomedical research, intent to participate in biomedical research in the future, and participation in biomedical research and biospecimen donation among a diverse, multilingual, community‐based sample across 3 distinct geographic areas. Methods: Three National Cancer Institute–designated cancer centers engaged in community partnerships to develop and implement population health assessments, reaching a convenience sample of 4343 participants spanning their respective catchment areas. Data harmonization, multiple imputation, and multivariable logistic modeling were used. Results: African Americans, Hispanic/Latinos, and other racial minority groups were more likely to be offered opportunities to participate in biomedical research compared to whites. Access to care, history of cancer, educational level, survey language, nativity, and rural residence also influenced opportunity, intent, and actual participation in biomedical research. Conclusions: Traditionally underserved racial and ethnic groups reported heightened opportunity and interest in participating in biomedical research. Well‐established community partnerships and long‐standing community engagement around biomedical research led to a diverse sample being reached at each site and may in part explain the current study findings. However, this study illustrates an ongoing need to establish trust and diversify biomedical research participation through innovative and tailored approaches. National Cancer Institute–designated cancer centers have the potential to increase opportunities for diverse participation in biomedical research through community partnerships and engagement. Additional work remains to identify and address system‐level and individual‐level barriers to participation in both clinical trials and biospecimen donation for research. Abstract : Engaging diverse populations in biomedical research and biospecimen donation remains a national challenge. The current study examines factors associated with biomedical research participation in diverse, multilingual, community‐based samples across 3 distinct geographic areas.